Pertanggungjawaban Perdata Dokter atas Tindakan Medis Terhadap Pasien - Sunarjo, Andreuw; Sudarto, Sudarto (FOCUS, 2025)
Medical practice is a service that is in the form of providing assistance or assistance based on patient trust in the doctor and is not a business relationship that is solely oriented towards profit, so the achievement of the medical contract is not the result that will be achieved, but a serious effort. In carrying out their obligations, doctors can make mistakes or negligence when carrying out their profession which is called malpractice. Medical malpractice is not mentioned in the legal regulations on health law or medical practice law in Indonesia because the elements of medical malpractice in the form of errors or negligence have been accommodated in the ethical guidelines and guidelines for the discipline of health service practices as well as from the side of health services and medical practice. For that, it will be further studied how the regulation of civil liability of doctors for medical actions towards patients is based on the laws in Indonesia and how the civil liability of doctors for medical actions towards patients is based on judicial practices in Indonesia. The research method used in this study is the normative legal research method. From the results of the study, it was found that the regulation of civil liability of doctors for medical actions towards patients is in Article 32 letter q of Law 44/2009 in conjunction with Article 66 of Law 29/2004 in conjunction with Article 1238-1239 in conjunction with Article 1365-1366 of the Civil Code in conjunction with Article 23 of PP 32/1996 and the civil liability of doctors for medical actions towards patients by compensating the patient for both material and immaterial losses. The civil liability of doctors for medical actions must be an unlawful act (onrechtmatigedaad), the medical personnel have committed an unlawful act because their actions are contrary to the care and careful attitude expected of them. From the research results for improvement, it is expected that Special Legislation will be made regarding Civil Liability of Doctors for Medical Actions Against Patients in the Law, Legislation, Government Regulations, Permenkes and the Supreme Court and/or Kemenkes issue PERMA, PERMENKES to clarify Civil Liability of Doctors for Medical Actions Against Patients